The Role of Higher Education Institutions Plays in Supporting Chinese International Students (Journal of Education and Development, 2022)
Chinese international students play a crucial role in the United States' higher education systems. China remains the top source of international students in the United States, sending more than 372,000 students to the United States from 2020-to 2021. This literature review explicitly focused on Chinese international students. Acknowledging that this student group has both positive and negative experiences interacting with the United States education system, existing research is more likely to focus on individual factors. However, higher education institutions' support systems are playing vital roles in the success of Chinese international students. I looked into issues with existing supports. After reviewing the existing literature, I suggest better support for international Chinese students and future research to consider the linguistic background of research participants and acknowledge international students' heterogeneity. Finally, I conclude by recommending future research that includes more culturally sensitive longitudinal studies, focus group discussions, and relationship building.